Novel tricyclic diamines 1. Synthesis of 1, 4-diazaisotwistane and 1, 4-diazahomoisotwistane as constrained 3-aminoquinuclidine isosteres. Issue 8 (21st February 2018) - McDonald, Ivar M.; Ng, Alicia; Cutrone, Jingfang; Mate, Robert; Olson, Richard E.
Graphical abstract: Highlights: Novel 1, 4-diazaisotwistane and 1, 4-diazahomoisotwistane tricylic diamines prepared as aminoquinuclidine isosteres. Synthesis relies on saturation of aromatic heterocycle followed by intramolecular cyclization. Structures of novel tricycles confirmed by X-ray crystallography. Abstract: Synthesis of the novel tricyclic diamines 1, 4-diazaisotwistane and 1, 4-diazahomoisotwistane are described. These compact tricyclic cores have one tertiary and one secondary amine and may serve as ring-constrained isosteres of 3-aminoquinuclidine. Both tricycles were prepared by a similar strategy involving saturation of an appropriately substituted aromatic azaindole, functionalization and intramolecular alkylation.